Recent Update on Applications of Quaternary Ammonium Silane as an Antibacterial Biomaterial: A Novel Drug Delivery Approach in Dentistry - Bapat, Ranjeet Ajit; Parolia, Abhishek; Chaubal, Tanay; Yang, Ho Jan; Kesharwani, Prashant; Phaik, Khoo Suan; Lin, Seow Liang; Daood, Umer (Frontiers in Microbiology, 2022)
Quaternary ammonium silane [(QAS), codename- k21] is a novel biomaterial developed by sol-gel process having broad spectrum antimicrobial activities with low cytotoxicity. It has been used in various concentrations with maximum antimicrobial efficacy and biocompatibility. The antimicrobial mechanism is displayed via contact killing causing conformational changes within the bacterial cell membrane, inhibiting Sortase-A enzyme, and causing cell disturbances due to osmotic changes. The compound can attach to S1’ pockets on matrix metalloproteinases (MMPs) leading to massive MMP enzyme inhibition making it one of the most potent protease inhibitors. Quaternary ammonium silane has been synthesized and used in dentistry to eliminate the biofilm from dental tissues. QAS has been tested for its antibacterial activity as a cavity disinfectant, endodontic irrigant, restorative and root canal medication and nano carrier for drug delivery approaches. The review is first of its kind that aims to discuss applications of QAS as a novel antibacterial biomaterial for dental applications along with discussions on its cytotoxic effects and future prospects in dentistry.